Hidden Dramas of Masculinity: Women’s Perspectives on Intimate Violence in Different Social Classes - Ptacek, James (Violence against women, 2021)
While intimate violence against women occurs in all social classes, few studies have examined this abuse in the context of both class privilege and class disadvantage. This research investigates the experiences of women from all social classes who were abused by intimate male partners. One key issue in this study concerns masculinities. Drawing from in-depth interviews with 60 women, what kinds of masculinity do abusive men present in public? How do these public masculinities contrast with the masculinities they embody in private? What are abusive men’s attitudes toward women in general? And finally, what similarities and differences do women report across social classes? Women reported that the different faces of masculinity men displayed helped to conceal the abuse and caused them to feel trapped in abusive relationships. This is interpreted in the context of masculinities and social class.